Second rapid assessment of food and nutrition security in the context of COVID-19 in Bangladesh - Food and Agricultural Organization of the United Nations; Ahmed, Akhter; Bakhtiar, M. Mehrab (Food and Agricultural Organization of the United Nations, 2020)
FAO Bangladesh coordinated this Second rapid assessment of food and nutrition security in the context of COVID-19 in Bangladesh to understand the impacts of the COVID-19 pandemic and the responses to it, on food and nutrition security in Bangladesh. The Consultative Group on International Agricultural Research (CGIAR), the International Food Policy Research Institute (IFPRI), the International Maize and Wheat Improvement Center (CIMMYT), the International Rice Research Institute (IRRI), and WorldFish, made significant contributions to this combined assessment. The assessment was completed in 30 days, including information collection, report drafting, peer review and finalisation. FAO and CGIAR experts collected the information mostly through telephone interviews with government counterparts, private sector actors, producer associations and other key informants.